Performance of CMIP6 HighResMIP Simulations on West African Drought - Ajibola, Felix Olabamiji; Zhou, Botao; Shahid, Shamsuddin; Ali, Md. Arfan (Frontiers in Earth Science, 2022)
This study evaluated the performance of seven CMIP6 HighResMIP models in the simulations of drought over two sub-regions of West Africa: the Guinea coast and the Sahel during the historical period of 1985–2014, in terms of the potential evapotranspiration index (PET), climatic water availability (CWA), and standardized precipitation evapotranspiration index (SPEI) at three time scales (i.e., 1, 3, and 12 months). The Climate Research Unit (CRU) TS v4.03 datasets were used as the observation reference. The observation shows that the PET and CWA during August (i.e., the rainfall annual peak) were less than 30 and 200 mm/month over the Guinea coast, respectively. The corresponding values over the Sahel were 100 and -50 mm/month, respectively. A significant decreasing trend was observed in drought over the Guinea coast (except Nigeria) and the Sahel. The frequencies of extreme and severe droughts were observed over Nigeria, Liberia, and Sierra Leone during the historical period. The seven HighResMIP models show different behaviors in simulating all of the abovementioned observation features. Among all the simulations, the ENSEMBLE, ECMWF, and IPSL generally perform better in almost all the statistical indices used, although there are still biases that need to be resolved in the models.